Preliminary acoustic analyses of the structure of Red-billed Leiothrix Leiothrix lutea (Scopoli, 1786) song samples from Northern Italy (Avocetta, 2022)
The authors present an introductory piece of research concerning the acoustic analysis of a set of song samples of Red-billed Leiothrix Leiothrix lutea from two regions of Northern Italy (Veneto, Liguria). By using an R package to analyze and find variations in the structure of the species' male songs, the count of the number of sound events detected, and the duration of pause event, show the most significant differences; moreover, the duration of signal events turns out to be different. The limited sample and the current lack of specific studies for comparison do not allow the authors to speculate whether the said variations are attributable to interindividual variability or geographic isolation and habitat adaption: further research from wider geographic areas is no doubt needed, also using the methods we followed, to make the analysis replicable.